Implementation of Computerized Physician Order Entry is Associated With Increased Thrombolytic Administration for Emergency Department Patients With Acute Ischemic Stroke - Ballard, Dustin W. (Ann Emerg Med, 2015)
OBJECTIVE: Electronic Health Record (EHR) systems with computerized physician order entry (CPOE) and condition-specific order sets are intended to standardize patient management and minimize errors of omission. However, the impact of these systems on disease-specific process measures and patient outcomes is not well established. We sought to evaluate the impact of CPOE-EHR implementation on process measures and short-term health outcomes for patients hospitalized with acute ischemic stroke. METHODS: We conducted a quasi-experimental cohort study of patients hospitalized for acute ischemic stroke with concurrent controls that took advantage of the staggered implementation of a comprehensive CPOE-EHR across 16 medical centers within an integrated healthcare delivery system from 2007 to 2012. The study population included all patients admitted to the hospital from the Emergency Department (ED) for acute ischemic stroke with an initial neuroimaging study within 2.5 hours of ED arrival. We evaluated the association between the availability of a CPOE-EHR and the rates of 1) ED intravenous tissue plasminogen activator (IV tPA) administration, 2) hospital-acquired pneumonia (PNA) and 3) inhospital and 90-day mortality using doubly robust estimation models to adjust for demographics, comorbidities, secular trends, and concurrent primary stroke center certification status at each center. RESULTS: Of 10,081 eligible patients, 6,686 (66.3%) were treated in centers after CPOE-EHR had been implemented. CPOE was associated with significantly higher rates of IV tPA administration (rate difference 3.4%, 95% CI; 0.8%, 6.0%) but not with rate differences in PNA or mortality. CONCLUSIONS: For patient hospitalized for acute ischemic stroke, CPOE use was associated with increased use of IV tPA.